2012
DOI: 10.1097/mol.0b013e328357e837
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial mechanosensors of shear stress as regulators of atherogenesis

Abstract: The discovery of a connection between endothelial cell structures such as cilia, integrin, extracellular matrix, and signaling events opens today a new chapter in our understanding of the molecular mechanisms regulating vascular responses to the changes in flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 63 publications
0
35
0
1
Order By: Relevance
“…Endothelial cells are equipped with a variety of factors to detect mechanical stimuli (Ando and Yamamoto 2013;Zaragoza et al 2012;Chatzizisis et al 2007). The long protruding primary cilium (Egorova et al 2012), glycocalyx, G-protein coupled receptors (GPCRs) (Chachisvilis et al 2006), ion channels (Ranade et al 2014), receptor tyrosine kinases (RTKs), and caveolae are present at the cell's apical surface in contact with the bloodstream.…”
Section: Mechanosensitive Systems Of Endothelial Cellsmentioning
confidence: 99%
“…Endothelial cells are equipped with a variety of factors to detect mechanical stimuli (Ando and Yamamoto 2013;Zaragoza et al 2012;Chatzizisis et al 2007). The long protruding primary cilium (Egorova et al 2012), glycocalyx, G-protein coupled receptors (GPCRs) (Chachisvilis et al 2006), ion channels (Ranade et al 2014), receptor tyrosine kinases (RTKs), and caveolae are present at the cell's apical surface in contact with the bloodstream.…”
Section: Mechanosensitive Systems Of Endothelial Cellsmentioning
confidence: 99%
“…Transport into the local tissue bed requires permeability of the endothelium, cell membrane and other vascular barriers (Komarova and Malik 2010;Zaragoza et al 2012). When administered systemically, only a small fraction of the injected drug ever reaches the target tissue, with the rest circulating through the healthy tissue, resulting in dose-limiting toxic side effects (Hanahan and Weinberg 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The geometric distribution of mechanical stress is closely associated with site-specific susceptibility to pathological changes [1,2,18,103], such as atherosclerosis and inflamma-tion in arteries, suggesting the effects of mechanical stress on the phenotypic changes of ECs and vascular wall. Clinical studies suggested that the sites of atherosclerosis are not random, but preferentially located at arterial branches and curvatures where the local flow is disturbed.…”
Section: The Interaction Between Mechanosensors and Mechanical Stressmentioning
confidence: 99%